Altered Homotopic Functional Connectivity Within White Matter in the Early Stages of Alzheimer’s Disease - Wang, Pan; Wang, Zedong; Wang, Jianlin; Jiang, Yuan; Zhang, Hong; Li, Hongyi; Biswal, Bharat B. (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder with memory loss and cognitive impairment. The white matter (WM) BOLD signal has recently been shown to provide an important role in understanding the cerebral intrinsic activity. Although the altered homotopic functional connectivity within gray matter (GM-HFC) has been examined in AD, the abnormal HFC to WM remain unknown. The present study sought to identify changes in the WM-HFC and anatomic characteristics by combining the fMRI with Diffusion Tensor Imaging (DTI). Resting-state and DTI magnetic resonance images were collected from the OASIS-3 dataset and consisted of 53 mild cognitive impairment patients (MCI), 90 very MCI (VMCI), and 100 normal cognitive (NC) subjects. Voxel-mirrored HFC was adopted to examine whether WM-HFC was disrupted in VMCI and MCI participants. Moreover, DTI technique was used to investigate whether specific alterations of WM-HFC were associated with anatomic characteristics. Support vector machine analyses were used to identify the MCI and VMCI participants using the abnormal WM-HFC as the features. Compared to NC, MCI and VMCI participants showed significant decreased GM-HFC in the middle occipital gyrus and inferior parietal gyrus, and decreased WM-HFC in the bilateral middle occipital and parietal lobe-WM. In addition, specific WM-FNs alteration for the bilateral sub-lobar-WM was found in MCI subjects. MCI subjects showed abnormal anatomic characteristics for bilateral sub-lobar and parietal lobe-WM. Results of GM-HFC mainly showed common neuroimaging features for VMCI and MCI subjects, while analysis of WM-HFC showed specific clinical neuromarkers and effectively compensated for the lack of GM-HFC to distinguish NC and VMCI and MCI subjects.